A fluorescent bead-based multiplex assay for the detection of Brucella sp. specific antibodies in canine serum - Guarino, Cassandra; Franklin-Guild, Rebecca; Asbie, Sanda; Pinn-Woodcock, Toby; Sipka, Anja Serap; Eade, Colleen; Griggs, Lauren; Altier, Elizabeth; Ceres, Kristina; Grohn, Yrjo; Altier, Craig; Wagner, Bettina (Frontiers in Microbiology, 2025)
IntroductionThe zoonotic pathogen, Brucella canis, causes brucellosis in dogs. Infection with B. canis is usually diagnosed by serological testing. We developed a fluorescent bead-based multiplex assay for detection of B. canis specific antibodies in canine serum. The assay consists of two antigens detected simultaneously by canine serum antibodies. One antigen, BP26, was selected from a set of immunodominant proteins identified through western blot and proteomics analysis. The second antigen, PO1, is a 17 amino acid peptide derived from B. canis Omp31.MethodsDog sera from diagnostic submissions were tested in parallel with a reference assay consisting of a rapid slide agglutination test (2ME-RSAT) and an agar gel immunodiffusion test (AGID II). A Bayesian latent class model (BLCM) was utilized to determine sensitivity and specificity of both assays. For the model to be identifiable, two groups with differing prevalence were included; one group was composed of 1,192 diagnostic submissions, and the second group was composed of 390 samples submitted for export purposes.ResultsThe seroprevalence of B. canis specific antibodies in these two groups was estimated to be 16.1% (95% CI, 12.6–19.3%) and 0.1% (95%, 0.0–0.6%), respectively. Diagnostic sensitivity and specificity of the two-antigen assay for detecting B. canis specific antibodies were 91.6% (95% CI, 85.2–98.0%) and 94.9% (95% CI, 92.3–96.9%), respectively.DiscussionThe addition of a third cytoplasmic antigen further increased assay sensitivity. The Canine Brucella Multiplex assay is a novel and quantitative diagnostic tool for detecting B. canis antibodies in canine serum to aid in the diagnosis of brucellosis in dogs.